Barbican building dispute, 1967 (London, 1967)
1967 1961-70 "Barbican building dispute, 1967" [BW0173], 1967, Trades Union Congress Between 1965-1967, there were a series of disputes on Myton Ltd's Barbican redevelopment site in the City of London. Following several dismissals, there was a thirteen-month lock-out and strike of all workers October 1966 - November 1967. The strike centred on disputes about bonus payments for various crafts, but also on issues related to sub-contracted casual workers on the 'lump'. In March, union officials agreed to a return to work of all except the works committee, but other workers would not return without them and the unofficial strike continued. The chief convenor, Lou Lewis, was expelled from his union, the Amalgamated Society of Woodworkers. After Myton dismissed the whole workforce and attempted to bring in new recruited labour through the picket line in April, the mood rapidly became more bitter and throughout the following months violence sporadically flared between pickets and police. The strike ended in November 1967 with the re-employment of most strikers. However, Myton's refused to re-employ six members of the Workers Committee, including Lou Lewis, who were then blacklisted in the industry.